Harnessing membrane trafficking to promote cancer spreading and invasion: The case of RAB2A - Kajiho, Hiroaki (Small GTPases, 2017)
How cancer disseminates and metastasizes remains an outstanding open question. Emerging evidence indicates that membrane trafficking is frequently harnessed by tumors of epithelial origin to acquire a mesenchymal program of invasiveness. However, the critical molecular hubs used by cancer cells this context have only began to be elucidated. Here, we discussed the results of a recent phenotypic screening that led to the identification of the small GTPase RAB2A, not previously involved in cancer dissemination, as pivotal for the acquisition of pericellular proteolysis, cell dissemination and distant metastatic spreading of human breast cancer. At the cellular levels, RAB2A controls both canonical polarized Golgi-to-Plasma membrane trafficking of the junctional protein E-cadherin, and post-endocytic trafficking of the membrane-bound metalloprotease, MT1-MMP. This finding reveals an unexpected plasticity in the control of diverse trafficking routes exerted by RAB2A through canonical (Golgi stacking) and non-canonical (late endosome recycling) functional interactions, contributing to break established membrane trafficking dogma on the rigorous molecular distinction between polarized Golgi and post endocytic routes. Finally, they suggest that epithelial cancers may specifically select for those molecules that enable them to control multiple trafficking routes, in turn essential for the regulation of activities necessary for acquisition of mesenchymal traits.